Maintenance of interphase chromosome compaction and homolog pairing in Drosophila is regulated by the condensin cap-h2 and its partner mrg15. - Smith, H.F.; Roberts, M.A.; Nguyen, H.Q.; Peterson, M.; Hartl, T.A.; Wang, X.J.; Klebba, J.E.; Rogers, G.C.; Bosco, G. (Genetics, 2013)
Dynamic regulation of chromosome structure and organization is critical for fundamental cellular processes such as gene expression and chromosome segregation. Condensins are conserved chromosome-associated proteins that regulate a variety of chromosome dynamics, including axial shortening, lateral compaction, and homolog pairing. However, how the in vivo activities of condensins are regulated and how functional interactors target condensins to chromatin are not well understood. To better understand how Drosophila melanogaster condensin is regulated, we performed a yeast two-hybrid screen and identified the chromo-barrel domain protein Mrg15 to interact with the Cap-H2 condensin subunit. Genetic interactions demonstrate that Mrg15 function is required for Cap-H2-mediated unpairing of polytene chromosomes in ovarian nurse cells and salivary gland cells. In diploid tissues, transvection assays demonstrate that Mrg15 inhibits transvection at Ubx and cooperates with Cap-H2 to antagonize transvection at yellow. In cultured cells, we show that levels of chromatin-bound Cap-H2 protein are partially dependent on Mrg15 and that Cap-H2-mediated homolog unpairing is suppressed by RNA interference depletion of Mrg15. Thus, maintenance of interphase chromosome compaction and homolog pairing status requires both Mrg15 and Cap-H2. We propose a model where the Mrg15 and Cap-H2 protein-protein interaction may serve to recruit Cap-H2 to chromatin and facilitates compaction of interphase chromatin.